The hypothalamus-pituitary-adrenal axis - Del Rey, Adriana; Chrousos, George P.; Besedovsky, Hugo O.; ScienceDirect eBooks (Amsterdam ; London : Elsevier, 2008)
The hypothalamic-pituitary-adrenal axis controls reactions to stress and regulates various body processes such as digestion, the immune system, mood and sexuality, and energy usage. This volume focuses on the immune system and provides substantive experimental and clinical data to support current understanding in the field, and potential applications of this knowledge in the treatment of disease. * Evidence presented in this book suggests that the Nervous -, Endocrine, - and Immune Systems form the Neuroendoimmune Supersystem, which integrates all the biological functions of higher organisms both in health and disease for their entire life cycle. * Contributors include both the scientists who initiated the work on the HPA axis and on the autonomic nervous system, and those who joined the field later.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Hypothalamic-pituitary-adrenal axis; MEDICAL -- Neuroscience; PSYCHOLOGY -- Neuropsychology; Hypothalamic-pituitary-adrenal axis; Hypothalamo-Hypophyseal System -- physiology; Hypothalamo-Hypophyseal System -- physiopathology; Electronic books